ANALISIS KESULITAN SISWA SMP KELAS VIII DALAM MENGERJAKAN SOAL CERITA ARITMATIKA SOSIAL - Nurul Dwi Pratiwi; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research was conducted to analyze the mistakes of student of class VIII at Mahardhika Junior High School in working on social arithmetic materials. This research is based on the importance of social arithmetic materials, which can be useful for students in their lives. The research method used is qualitative descriptive research method. The population of this research was 20 students of class VIII D. Then, the results of this research were obtained from students answers after students were given C1-C6 questions as many as 6 questions. Technical analysis used is to assess the student's answer based on 6 C1-C6 questions that have been given, followed by observing the many mistakes students have in solving the quetion. From the results of the analysis, there are some students who do not understand the formula to do the problem, some students also still do not understand in changing the problem into the math sentence that should be, and some other students still have difficulty in procedural work such as the use of calculating operations in doing problems. So looking at these results, it can be concluded that the ability of students in doing problems, especially social arithmetic materials, is still said to be relatively low.